18 Heart failure patient and caregiver needs and expectations regarding self-management via digital health – the passion-HF project. (30th September 2020) - Palant, A; Zippel-Schultz, B; Brandts, J; Eurlings, C; Barrett, M; Murphy, M; Furtado Da Luz Brzychcyk, E; Hill, L; Dixon, L; Fitzsimons, D; Ski, CF; Thompson, DR; et al.
Abstract : Background: Current heart failure (HF) healthcare services are not sufficient to meet the needs of an aging population with increasing comorbidities and disease complexity together with the unequal distribution of medical care in rural and urban regions. These factors have created an imminent need to identify alternative healthcare approaches. eHealth applications have potential to alleviate much of the burden on healthcare services and improve patient treatment. The 'PASSION-HF' project aims to develop a digital decision support system – a virtual doctor – that provides solutions based on current clinical guidelines. Patient independence is maximized through 24/7 access to personalized HF management. Furthermore, the application (named DoctorMe) defines processes and decision points where medical professionals need to be included in the process. Purpose: To understand the needs and requirements of HF patients and their informal caregivers in regard to a virtual doctor. Methods: We conducted an exploratory mixed-method study within the Netherlands, United Kingdom, Ireland and Germany. Qualitative, guided interviews were supplemented by a standardized questionnaire. The interviews focused on acceptance factors, motivation to use a decision support system and satisfaction with their current health care situation. Interviews were analysed using the content analysis according to Mayring (2010) with the help of 'Atlas.TI' software. Supplementary questionnaires on self-management of HF-patients, the role of the informal caregivers, technology acceptance, and decision making. Results: A total of 49 patients and 33 informal caregivers were interviewed. Patients were male (76%) aged between 60 and 69 years (43%). Three key themes were identified in regard to digital health: 1) Reassurance: patients often feel uncertain about their condition and their symptoms and a need for instant feedback about their current health status; 2) Personalized advice: patients want a system that can adapt medication, sport activities and food recommendations to their current health status; 3) Transparency: patients want to know the source, reasons, and individualized interpretation of any recommended changes to the management of their condition. Additionally, patients have a desire to adapt their lifestyle to the needs of HF, but they require help to remain motivated to achieve this goal. Conclusion: These findings provide valuable information for the development and implementation of eHealth solutions. Patients want reassurance 24/7, independently of the availability of healthcare services, combined with personalized medical advice regarding day-to-day management of their HF. In a next step, we are planning a multicentre clinical trial to test the first prototype of the eHealth product (DoctorMe).